E-waste recycling behaviour with reference to consumers in Kuantan city - Yong, Yee Leng; Muhammad Arif, Afida Mastura (Human Resource Management Academic Research Society, 2022)
Managing e-waste among consumers poses significant challenges for the authorities, as proper e-waste management is more prevalent in industrial sectors than in households. Consumers are left to manage their household e-waste in a disorganised manner either by throwing it in the trash or dumping it illegally. This study seeks to fill this gap by identifying the factors that influence consumer e-waste recycling behaviour. A quantitative approach was adopted for this study and a survey data was collected from 200 households through systematic sampling method. The results for Pearson correlation coefficient showed that awareness (r = 0.553, p = .000), availability of facilities (r = 0.260, p = .000) and perceived behavioural control (r = 0.341, p = .000) were significantly and positively associated with consumer e-waste recycling behaviour. The results for multiple linear regression showed that adjusted R2 is 0.336 which indicated that the determinants were able to predict 33.6% of the consumer e-waste recycling behaviour. Awareness and perceived behavioural control were significant determinants for consumer e-waste recycling behaviour among households while the most influential factor is awareness. The findings of this study would able to help the relevant authorities to increase the awareness of consumers to participate in e-waste recycling through campaigns and educational activities.